(The Effect of A Strategy (Note - Reflect - Explanation) on The Achievemen And Tha Habits of The Mind Among The Second -Grade Students In The Subject of Science) (Journal of the College of Basic Education, 2024)
The research aims to identify the "effect of the (Notice - Reflect - Explain) strategy on the thinking habits of second-grade middle school students in the subject of science." From this, the following null hypothesis was derived:"There is no statistically significant difference at a significance level of 0.05 between the mean scores of the experimental group students who will be taught using the (Notice - Reflect - Explain) strategy and the mean scores of the control group students who will be taught using the conventional method in the Mind Habits Scale."The experimental design with two groups, experimental and control, was purposively chosen from the participants of the post-test of the Mind Habits Scale. The current research community represents the second-grade middle school students studying in all government-run daytime middle schools affiliated with the General Directorate of Education in Baghdad/Al-Rusafa Al-Ula for the academic year (2022-2023). Habib Allah Boys' Intermediate School was selected as a purposive sample for the current research among the schools in the community. The total sample size for the research was 61 students for both the experimental and control groups. The students were matched in variables such as previous achievement, intelligence, prior knowledge, and the Mind Habits Scale. The experiment was conducted in the first semester of the academic year (2022-2023), and the current research focused on the first four chapters of the science textbook. A total of 183 behavioral objectives were prepared according to Bloom's taxonomy levels (Remember, Understand, Apply, Analyze, Evaluate, Create).To test the validity of the null hypothesis, the researcher constructed the Mind Habits Scale according to Daniel's four-dimensional model, consisting of 32 items. Twelve items were taken for equivalence purposes, and twenty items were included in the final Mind Habits Scale. The apparent validity of the tool was verified, with the stability of the Mind Habits Scale reaching a Cronbach's alpha of 0.87. After completing the experiment and applying the Mind Habits Scale to the students of the current research sample (control and experimental), appropriate statistical methods were used to analyze the data. The results showed the superiority of the experimental group students who were taught using the (Notice - Reflect - Explain) strategy over the control group students who were taught using the conventional method in the Mind Habits Scale.Based on the research results, the researcher concluded the following:- Teaching second-grade middle school students using the (Notice - Reflect - Explain) strategy had a positive effect on improving their thinking habits.Based on this, the researcher provided a number of recommendations and suggestions.